Transformations of Main-Group Organometallics Induced by Transition Metals - Hirao, Toshikazu; Amaya, Toru (Synlett, 2022)
The oxidative dehydrometallation of silyl or boron enolates is induced by palladium(II) catalyst to result in the versatile introduction of α,β-unsaturated carbon–carbon double bonds via palladium enolates. Selective oxidative cross- and homo-coupling reactions of silyl or boron enolates induced by vanadium(V) oxidant provide a selective synthetic method for accessing 1,4-dicarbonyl compounds in a nucleophile-nucleophile coupling mode. The ligand coupling reaction of main-group organometallic compounds induced by vanadium(V) oxidant provides a unique method for intramolecular carbon–carbon bond formation of nucleophiles. The last two reactions are a complementary strategy for the nucleophile-electrophile coupling reaction. The dehydrometallation and coupling reactions probably proceed through two- and one-electron oxidation processes, respectively.1 Introduction2 Palladium-Catalyzed Dehydrometallation3 Homo- and Cross-Coupling of Main-Group Organometallic Compounds4 Oxidative Ligand Coupling of Main-Group Organometallic Compounds5 Conclusion
Keywords: dehydrosilylation; boron enolates; palladium enolates; dehydroboration; α,β-carbon–carbon double bonds; 1,4-diketones; ligand coupling; main-group organometallics